Panayotis J. Tsakonas, The incomplete breakthrough in Greek-Turkish relations. Grasping Greece’s socialization strategy, Paigrave Macmillan, Basingstoke - New York 2010, xi & 289 σελ. - Ροζάκης, Χρήστος (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2017)
Δεν διατίθεται περίληψη / no abstract available